Review of the Meaning of Life on Widows - Christianti Rebeca Pombu; Juliana Marlin Y. Benu; Indra Yohanes Kiling (Journal of Health and Behavioral Science, 2021)
The event of losing a spouse will be even heavier when seen by women. This made a woman have to assume a new status as a widow. This changing status and role led to major changes in his life. A person who experiences disappointing events in life will feel the emptiness in the meaning of life. And creating a meaningful life is the responsibility of the individual and cannot be entrusted to others because she must feel and experiences it. This literature review explore theories and literature on the meaning of life and its context in widows. More studies on how widows discover meaning in their life are needed to help improve their overall well-being.